Effects of palygorskite composites on growth performance and antioxidant status in broiler chickens. (19th February 2019) - Yan, Rui; Hui, Aiping; Kang, Yuru; Zhou, Yanming; Wang, Aiqin
ABSTRACT: This work aimed to investigate the effects of the palygorskite (PAL ) composites on the growth performance and antioxidant status in broiler chickens. A total of 192 one-day-old Ross 308 broilers were randomly divided into 3 treatment groups. Broilers were fed basal diets supplemented with either 50 mg/kg chlortetracycline (CTC group), 1 g/kg ZnO/PAL (ZnO/PAL group), or 1 g/kg chitooligosaccharides/ZnO/PAL (COS/ZnO/PAL group), respectively. The results showed that PAL composites were found to exhibit similar effects on growth performance as CTC ( P > 0.05). ZnO/PAL and COS/ZnO/PAL enhanced the activity of serum glutathione peroxidase (GSH-Px ) compared with CTC both at 21 and 42 d ( P < 0.05). Compared with the CTC group, COS/ZnO/PAL enhanced serum catalase (CAT ) activity at 21 d ( P < 0.05), and decreased serum malondialdehyde (MDA ) content at 42 d ( P < 0.05). Compared with the CTC group, ZnO/PAL decreased duodenal mucous MDA content at 21 d, while ZnO/PAL did not affect activities of superoxide dismutase (SOD ) and GSH-Px in the duodenum ( P > 0.05). The duodenal mucous activities of SOD and GSH-Px were the highest in the COS/ZnO/PAL group at 42 d ( P < 0.05). At 21 d, broilers in the COS/ZnO/PAL group had the lowest MDA content and the highest total antioxidant capacity (T-AOC ) in the jejunum ( P < 0.05). Palygorskite composites decreased ileum mucous MDA content compared with CTC treated broilers at 21 d ( P < 0.05). At 42 d, ileum mucous T-AOC was increased both in the ZnO/PAL and COS/ZnO/PAL groups compared with the CTC group ( P < 0.05). The ileum mucous GSH-Px activities both in the ZnO/PAL and COS/ZnO/PAL groups were increased compared with the CTC group ( P < 0.05). In conclusion, the broilers given the basal diet supplemented with the PAL composites exhibited similar growth performance to their counterparts in the AGP group. Additionally, the PAL composites improved the antioxidant status of broilers and the beneficial effects of COS/ZnO/PAL on the antioxidant status are more pronounced.